GERAKAN KULTURAL ORGANISASI ETNIS DI KOTA SINGKAWANG DALAM MEMBANGUN HARMONI BERSAMA - Insani, Satya Putri (Studia Sosia Religia, 2023)
This study explores information about the cultural movement of ethnic organizations in the city of Singkawang in building harmony together. The existence of an organization like this is interesting to reveal, because Singkawang as a multi-ethnic city lives side by side with various tribes, the local community is very tolerant of its diversity. With diversity, cultural space really needs to be utilized in order to create inter-ethnic harmony in an effort to reduce conflict. This study uses Anthony Giddens' theory regarding social movements and is a type of field research (Lapangan). Researchers used a sociological approach, which is a type of qualitative research using descriptive methods. Data collected through observation techniques, interview guidelines and various scientific literature. Based on the results of the data obtained, this ethnic organization is one of the social movements proposed by Anthony Giddens which is carried out jointly by a group to achieve the same goal. The cultural movements of ethnic organizations in the city of Singkawang such as MABT, MABM, and DAD have the same goals and interests, namely to strengthen harmony and increase tolerance in the city of Singkawang so that harmony, peace and peace live through the applied cultures. First, the MABT cultural tradition of caring for tolerance and harmony by holding social service activities, then respecting each other at certain moments that become the culture of each religion such as: Chinese New Year, Cap Gomeh, Ramadan, and Christmas. In MABT, every problem is solved as a family. Second, MABM has the concept that if all ethnic religions run properly and correctly then there will be no clashes. to increase tolerance one must communicate frequently, through art, festivals, and mutual respect. while DAD is in maintaining harmony, namely coordinating, communicating across ethnicities and not acting on behalf of ethnicity and religion in solving problems. In addition to building harmony together, cultural movements are also a form of resilience between tribes, ethnicities, religions and even languages. One of the local cultures that cannot be separated from the customs of the people of Singkawang city is the installation and removal of decorations at the time of major celebrations.